Microbial interactions and metabolisms in response to bacterial wilt and black shank pathogens in the tobacco rhizosphere - Tang, Qianjun; Liu, Tianbo; Teng, Kai; Xiao, Zhipeng; Cai, Hailin; Wang, Yunsheng; Xiao, Yunhua; Chen, Wu (Frontiers in Plant Science, 2023)
Tobacco bacterial wilt (TBW) and black shank (TBS) are responsible for substantial economic losses worldwide; however, microbial interactions and metabolisms in response to bacterial wilt and black shank pathogens in the tobacco rhizosphere remain unclear. We explored and compared the response of rhizosphere microbial communities to these two plant diseases with the incidences in moderate and heavy degrees by sequencing of 16S rRNA gene amplicons and bioinformatics analysis. We found that the structure of soil bacterial communities was significantly (p < 0.05) changed from the incidences of TBW and TBS, which also led to decreased Shannon diversity and Pielou evenness. Compared with the healthy group (CK), the OTUs with significantly (p < 0.05) decreased relative abundances were mostly affiliated with Actinobacteria (e.g., Streptomyces and Arthrobacter) in the diseased groups, and the OTUs with significantly (p < 0.05) increased relative abundances were mainly identified as Proteobacteria and Acidobacteria. Also, molecular ecological network analysis showed that the nodes (<467) and links (<641) were decreased in the diseased groups compared with the control group (572; 1056), suggesting that both TBW and TBS weakened bacterial interactions. In addition, the predictive functional analysis indicated that the relative abundance of genes related to the biosynthesis of antibiotics (e.g., ansamycins and streptomycin) was significantly (p < 0.05) decreased due to incidences of TBW and TBS, and antimicrobial tests showed that some Actinobacteria strains (e.g., Streptomyces) and their secreted antibiotics (e.g., streptomycin) could effectively inhibit the growth of these two pathogens.